Comparison of the Clinical Outcomes and Efficiencies of HIFU (High-Intensity Focused Ultrasound), Da Vinci Robotic Surgery and Laparoscopic Surgery for Uterine Fibroids: A Systematic Review and Meta-Analysis - Altangerel Otgontuya; Cherng-Jye Jeng; Trong-Neng Wu; Linus T. Chuang; Jenta Shen (Clinical and Experimental Obstetrics & Gynecology)
Background: To compare the clinical outcomes and treatment efficiencies of advanced surgical treatments including High-Intensity Focused Ultrasound (HIFU), robotic surgery and laparoscopic surgery in the uterine fibroid patients. Methods: A total of 512 studies from 1995 to 2021 were identified by screening from Science Direct, Cochrane library, Medscape, Willey Online Library, PubMed, and Taylor Francis. From these studies 29 articles were qualitatively included in our systematic review and 24 of them considered quantitively eligible were included in the meta-analysis. Study analyzed by pooling the weighed mean difference (WMD) with the 95% confidence interval (CI) were study provided as a mean + (SD) and pooled risk ratio (RR) was expressed for dichotomous variables. Pooled results were assessed with either a random-effect or fixed-effect model. Heterogeneity was evaluated using the I2 statistic. Results: Comparison of HIFU and robotic surgeries with operation times of 86.13 ± 36.37 minutes to 120.2 ± 63 minutes and 166 ± 48.5 minutes to 278 ± 67 minutes were higher significant differences (I2 = 97%, p < 0.00001), (WMD –111.88 [–189.68, –34.08]) with statistically significant (p = 0.005). Comparison of HIFU and laparoscopic surgery in operation time of 86.13 ± 36.37 minutes to 120.2 ± 63 minutes and 79 ± 30 minutes to 106.4 ± 38.5 minutes were not statistically significant (p = 0.75) with higher significant differences heterogeneity (I2 = 96%, p < 0.00001), (5.51 [–27.82, 38.83]). Comparison of between blood losses and fibroid sizes at 154 ± 75 mL to 278 ± 164.6 mL and 6.5±2.9 cm to 13.6 ± 3.1 cm respectively in laparoscopic surgery was higher significant differences (I2 = 91%, p < 0.0007), (WMD 202.29 [87.77, 316.80]) with statistically significant (p = 0.0005). Between hospital stay and blood loss in laparoscopic surgery at 1.2 ± 0.9 days to 5.4 ± 0.2 days and 200 ± 107 mL to 278 ± 164.6 mL showed significant differences (I2 = 90%, p < 0.0001), (WMD –269.71 [–361.33, –178.09]) with statistically significant (p < 0.00001) while in robotic surgery was not significant. The follow up uterine fibroid symptom & health-related quality of life questionnaire (UF-QOL) at 3 months 45.3 + 26.9 to 70.6 + 26.9 in fibroids group and 61.6 + 41.4 to 79.64 + 17.91 in adenomyosis group and both shows significantly different (I2 = 83%, p = 0.02), (WMD 14.08 [4.42, 23.75]) with statistically significant (p = 0.0004) and (I2 = 97%, p < 0.00001), (WMD –15.95 [–28.06, –3.84]) with (p = 0.010). SSS follow up 3 months 27.2 + 15.7 to 36.6 + 7.9 in fibroids of HIFU, the heterogeneity test showed significant differences (I2 = 95%, p < 0.00001), (WMD 16.22 [8.33, 24.11]) with statistically significant (p < 0.0001). In terms of pregnancy outcome, delivery outcome in live birth between HIFU and laparoscopic surgery 4 (8) within 165 (219) and (7) 23 within 158 (224), the heterogeneity was not significant (I2 = 0%, p = 0.44), (RR 1.06 [0.97, 1.17]) neither with for risk of delivering was not significant (p = 0.20). Conclusions: HIFU treatment reveals more efficient clinical and treatment outcomes than robotic or laparoscopic surgery, including improved symptoms, absence of bleeding, shorter operative time, shorter recovery time, and good benefits in both short-term and long-term quality-of-life.